#### Answer

In order to factor by grouping, we arrange the terms in pairs and factor out the common factor for each pair, hoping to obtain an expression of the form
=(term 1)[expression 1]+(term 2)[expression 1],
that is, the brackets hold $\underline{the~same~expression}$.
If that is the case, we factor it out:
=[expression 1][(term 1) + (term 2) ]
---
For example,
$3x^{2}+3y^{2}x+2y^{2}x+2y^{4}=[3x^{2}+3y^{2}x]+[2y^{2}x+2y^{4}]$
$=3x(x+y^{2})+2y^{2}(x+y^{2})\quad $...same expression!
=$(x+y^{2})(3x+2y^{2})$

#### Work Step by Step

Given above.